Grundlagenuntersuchungen und Erarbeitung einer Methodik zur Herstellung maßgeschneiderter Halbzeuge auf Basis eines neuartigen flexiblen Walzprozesses - Vogel, Manfred (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
One of the greatest social challenges of the 21st century is the mitigation of climate change. One approach that has become increasingly important in recent years, especially in the automotive industry, is holistic lightweight construction, which is increasingly pushing conventional manufacturing technologies in the area of forming technology to their limits. By applying the innovative process class of sheet bulk metal forming, functional components with a high degree of functional integration can be manufactured in a process-safe, energy-and cost-optimized manner. The use of process-adapted semifinished products in particular has proven to increase material efficiency. In particular, incremental forming processes show a high potential. The aim of the present work is therefore to develop a holistic process understanding for the production of tailored blanks by means of a new flexible rolling process. To derive physical relationships, a fundamental experimental process and influence analysis is carried out and, based on this, a holistic methodology for the manufacturing of a rotationally symmetrical material pre-distribution is derived. Using the knowledge gained, the transferability of the methodology to higher-strength material classes and varying semi-finished product thicknesses, as well as the usability of the semi-finished products in a downstream combined deep-drawing and upsetting process is evaluate